The Effects of Stocking Density on Growth and Survival rate of Beong (Hemibagrus nemurus) - Wildah Faizati; Sri Hastuti; Ristiawan Agung Nugroho; Tristiana Yuniarti; Fajar Basuki; Dewi Nurhayati (Departemen Akuakultur FPIK UNDIP, 2021)
Beong are one of endogenous fish in Indonesia and still rely on catches from nature. The level of growth and survival rate in culture of beong is still low, so it is necessary to do cultivation efforts for conservation of beong, so that the beong can be cultivated intensively. One effort that can be do is biological manipulation in the form of stocking density. This study aims to determine the effect of shocking density on growth and survival rate and find out the best amount too. The study was conducted in April-May 2018 at UPT BBI Sawangan, Magelang, Central Java. The method used in this study was experiment method and Completely Randomized Design (CRD) for 4 treatments, 3 replicates with stocking dencities of A (10 fish/m2), B (30 fish/m2), C (50 fish/m2)and D (70 fish/m2). The results showed that different stocking densities gave a significant effect (Sig.> 0.05) on TKP, FCR, SGR and SR. This is allegedly due to feed competition, space competition and cannibalism in Beong fish. Treatment B gave the best results at TKP, FCR, SGR and SR with a value of 1.36 ± 0.01 gr / individual, 1.15 ± 0.11, 4.58 ± 0.22% / day and 83.33 ± 3,34%.